Islamic Radical Polemics and Terrorism in Indonesia From The Perspective of Islamic Figures and Literature - Agussani Agussani (UMSU, 2020)
Islam got a negative precedent by some particular people because of radicalism and terrorism issues. This study aims at identifying some prominent Islamic figures' opinions towards those issues and how the literature explains them. This study is a phenomenology research. The researcher collected the data of the study through interviews and documentation. Then, the collected data were analyzed qualitatively using an interactive model analysis. The results of the study show that: (1) the informants believe that radicalism and terrorism are caused by misunderstanding the concept of jihad by some particular people, and that misunderstanding brings negative precedent towards Islam; and (2) based on the explanation in several kinds of literature, Islam never teaches people to be radical or terrorists. People need to study the real meaning of the jihad concept. Besides, Islam is not rigid and does not depend on form. People can implement it within any framework of virtue and in any time dimension. Showing the face of Islam that rahmatan lil 'alamin will prevent Muslims from Huntington's trap so that Islam is not seen as radical and terrorist.